Shooting Movies: Effects of Gun and Firearm Exposure in Popular Films on Gun Use Self-Efficacy and Gun Attitudes/Beliefs - Lapierre, Matthew A.; Sada Garibay, Cecilia (SAGE Publications, 2025)
Gun violence in the United States is a public health crisis with debates raging about the role of guns in American society. The current study examined how exposure to guns in movies may shape attitudes/beliefs about guns and the mediating role of gun use self-efficacy as a potential mechanism for effects, using a retrospective survey with 612 undergraduates. Increased exposure to guns in movies was correlated with less support for gun control and stronger beliefs that guns make society safer. Importantly, gun use self-efficacy was a significant mediator between movie exposure and gun control. © The authors © SAGE.
Keywords: Guns and Firearms; Films